Estimation of a nonparametric regression spectrum for multivariate time series - Jan Beran; Mark A. Heiler (University of Konstanz, Center of Finance and Econometrics (CoFE), 2007)
Estimation of a nonparametric regression spectrum based on the periodogram is considered. Neither trend estimation nor smoothing of the periodogram are required. Alternatively, for cases where spectral estimation of phase shifts fails and the shift does not depend on frequency, a time domain estimator of the lag-shift is defined. Asymptotic properties of the frequency and time domain estimators are derived. Simulations and a data example illustrate the methods.
urn:nbn:de:bsz:352-opus-116674
Keywords: 330; Periodogram; cross spectrum; regression spectrum; phase; wavelets